Peran Brand Image Dalam Meningkatkan Loyalitas Tamu Hotel: Studi Pustaka - Oka Rei Nandi (Bajang Institute, 2026)
This study aims to analyze the role of Brand image in enhancing hotel guest loyalty through a literature review approach. The study is motivated by the increasing competition in the hospitality industry, requiring hotels to develop effective strategies to retain customers by establishing a strong and positive brand image. This research employed a qualitative method using a library research approach. Data were collected from national and international journal articles, academic books, and other scientific publications relevant to the topic and published between 2020 and 2026. Literature was retrieved from Google Scholar, Scopus, ScienceDirect, and Garuda databases. The collected data were analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that Brand image plays a significant role in improving hotel guest loyalty. A positive Brand image enhances customer trust, increases customer satisfaction, strengthens the emotional relationship between guests and the hotel, and encourages revisit intentions as well as positive word-of-mouth recommendations. Furthermore, the advancement of digital technology has made reputation management through social media and online reviews increasingly important in shaping hotel brand image. Therefore, strengthening Brand image is an effective strategy for improving guest loyalty while creating sustainable competitive advantages in the hospitality industry.